Monitoramento dos processos erosivos e da dinâmica hidrológica e de sedimento de uma voçoroca: estudo de caso na Fazenda do Glória na zona rural de Uberlândia-MG - Alves, Ricardo Reis (2007)
The study area is located in Uberlândia MG, in one of the experimental farms of the Federal University of Uberlândia, which is known as Glória Experimental Farm. The gully researched is located in a region of contact between Sand Stones and Basalts. In this place, the Humankind made a lot of interventions in the natural forms, and the most part of the vegetation was put down and the soil started to be used for agriculture and other Human uses. This study consists in to monitoring a gully activity, considering the erosive process engaged, the hydrological dynamics and the sediments transport. For collecting data in the field about these topics, it was necessary to construct a little dam at the mouth of gully flow, which used to improve data about water flow variation and the sediments transport, which were analyzed in the lab. Also was taken a lot of photos of the studied process, which were used in the lab analyses. The objectifies of this study were to show the influences of the erosive process by gullies in the equilibrium of the environment, specially because of the large quantity of sediments that is generated in this process. This gully is connected directly to a brook stream of inferior order of the Paraná Hydrologic Basin, and part of the large quantity of sediments produced in this gully can cause a lot of problems in Down Basin area, specially for the rivers channels and hydroelectric lakes. This shows that the problematic of gullies it is not intrinsic just to the loco where the gully is, but to all macro-basin where the gully is inserted.